Caracterização e veículação de extrato da casca do fruto da bacaba (Oenocarpus bacaba mart.) em sistemas Microemulsionados - Corrêa, Bruna Mendes (2018)
Oenocarpus bacaba Mart. is a palm tree native from Amazon forest with notable antioxidant activity attributed to its bioactive compounds. Its fruit (bacaba) processing dismisses the peel, which has bioactive compounds that can collaborate to its antioxidant activity and prevent diseases, being an interesting option to incorporate in formulations in order to create drug carriers with advantages. Thus, the aim of this work was assess the centesimal and mineral composition, physicochemical characterization (acidity, total soluble solids, pH, and color), total phenolics (Folin-Ciocalteu method), anthocyanins and antioxidant activity by DPPH (2,2 difenil-1-picril hidrazil) radical scavenging method in bacaba peels. As well as incorporate its extract in microemulsions to assess its stability and antioxidant potential. For the centesimal composition, the values found were 4.87, 1.42, 29.13, 1.08 and 63.32 g 100 g-1 contents for moisture, ashes, lipids, proteins, and total carbohydrates, respectively. For the mineral composition, the values found were 582.97, 79.00, 51.79, 0.625, 37.02, 2.37 and 77.12 mg 100g -1 contents for potassium, sodium, magnesium, copper, calcium, manganese, and phosphorus, respectively. The physicochemical characterization showed values of pH of 5,66, of titratable acidity of 0,306% of citric acid, total soluble solids of 9.75 ° Brix, and coordinates L* a* e b* of 19.03, 8.07 and 9.25, respectively. Phenolic contents were quantified as 42.07 mg EAG g-1 . The IC50 for the antioxidant potential was 1.07 mg mL-1 and anthocyanins 37.31 mg 100 g-1 . For the microemulsion formulation, it was used pre-established quantities of distilled water, capric/caprylic triglycerides, Span 80® and Tween 80® , with 5 % of extract at 0.1 g mL-1 added. From the 72 tested formulations, eight produced microemulsions and were subjected to centrifugation, physicochemical characterization (pH, electrical conductivity and refractive index) and stability studies, with four sustaining their physical stability after the tests. All approved samples showed Newtonian profile and linear viscosity. The mean droplets size of the formulations was 308 nm. The antioxidant potential was effective. Results showed that bacaba peels are an alternate source of nutrients and bioactive compounds, suggesting their potential use in food and cosmetic industries, especially due to their antioxidant activity and mineral composition. Regarding the microemulsions, the systems presented stability and antioxidant activity, showing suitable for use as carriers for drugs, cosmetics, among others.